Pengaruh Gaya Kepemimpinan Dan Upah Terhadap Kinerja Karyawan (Studi Kasus Pada PT. Dan Liris Kabupaten Sukoharjo) - Mardianti, Ratna; , Eko Sugiyono, Drs, M.Si (2016)
Considering its important was human resource to company, in Consequence Company have to pay attention the factors likes: leadership style and fee of very needed for all employees to increase performance in executing fundamental duty and responsibility. This research was aim to analyse the influence of leadership style and fee toward employee performance of PT. DAN LIRIS Grogol District Sukoharjo Regency. This research was representing the survey research, by questioner as a means of compiler of research data. Sum up the sample research counted 106 responders taken by purposive sampling. The data analysis technique was used multiple linear regressions analyze and hypothesis test covering F test, t test and coefficient determinasi R2 test. The results of analysis can be conclusion that the leadership style have an significant effect toward employee performance, was proven from t count value equal to 8,560 > t table (1,983), and fee have an significant effect toward employee performance, was proven from t count value equal to 2,629 > t table (1,983). So that hypothesis H1 and H2 was truth acceptable.